PHYSICIAN AND PHARMACIST OPINION ON DIABETES MELLITUS AND THE MOST COMMONLY PRESCRIBED ANTI-DIABETIC DRUG IN VARIOUS DISTRICTS OF U.P. (WEST), INDIA - Rastogi, Vaibhav; Kumar, Bhaskar; Kumar, Deepak; Kumar, Arvind; Porwal, Mayur; Yadav, Pragya; Prasad, Neelkant (Journal of Drug Delivery and Therapeutics, 2016)
Diabetes mellitus (DM) is a group of metabolic disorders characterized by a chronic hyperglycemic condition resulting from defects in insulin secretion, insulin action or both. The prevalence of diabetes is increasing rapidly worldwide and the World Health Organization indicates global prevalence of diabetes was estimated to be 9% among adults aged 18+ years and it will be the 7th leading cause of death in 2030. The aim of this paper is to gather latest information on the prevalence of Diabetes among the human society and also to investigate pharmaceutical marketing of Metformin and its combinations used for Diabetes Mellitus in various districts of U.P. (West) region. The survey was based on the questionnaire which was presented before the physicians and the pharmacist in-charge on medical store to get information about the patient having diabetes mellitus and commonly prescribed brands of Metformin alone and its combination with other anti-diabetic drugs. On the basis of physicianâ€™s opinion on the Diabetes (type 2), 65.78% of patients from total OPD patients was found to have diabetes,Â  49.76% patients are type-2 patients, 7.45% of teenagers was fall in the category of having type-1 diabetes and 8.57% were among the new patients of diabetes. There are 20 and 30 brands in Metformin (and its HCl salt), Metformin (and its HCl salt) with other anti-diabetic drug categories, respectively. The sale of Glyciphage of Franco Indian Remedies brand of the Metformin only, Diapride M 1 containing Glimepiride and Metformin 500 mg from Micro Labs Ltd., respective categories, were highest in the area of interest. KEYWORDS: Diabetes Mellitus, Metformin (and its HCl salt), Combination drugs, Marketing Investigation.